High nitrogen phosphorus ratios reduce nutrient retention and second-year growth of wetland sedges - Güsewell, Sabine (The New phytologist, 2005)
Shifts from nitrogen (N)- to phosphorus (P)-limited growth due to high N deposition may alter the functioning of wetland vegetation. This experiment tested how N vs P deficiency affects the growth and nutrient use of wetland sedges. Five wetland Carex species were grown at nine N : P supply ratios (0.6-405) with two absolute levels of N and P. Biomass and nutrient concentrations were determined after one and two growing seasons. Shoot biomass was maximal at N : P supply ratios of 15-26 after one season but 5-15 after two seasons. Photosynthesis after the first season, second-year growth, leaf longevity, and the fraction of nutrient supply retained by plants over two seasons were all negatively related to N : P supply ratios, with small effects of absolute supply. The five Carex species responded similarly to N : P ratios but differed in nutrient resorption efficiency and biomass allocation. Plants treated with high N : P ratios appeared to lose nutrients below ground. Such losses may reduce plant performance in P-limited wetlands affected by high N deposition